Procalcitonin, Interleukin-6 and C-reactive Protein Levels Predict Renal Adverse Outcomes and Mortality in Patients with Acute Type A Aortic Dissection - Chen, Xuelian; Zhou, Jiaojiao; Fang, Miao; Yang, Jia; Wang, Xin; Wang, Siwen; Yang, Lichuan (Frontiers in Surgery, 2022)
Background Acute type A aortic coarctation (AAAD) is a highly deadly and serious life-threatening disease. The purpose of this study was to estimate the predictive value of peak procalcitonin, interleukin-6, and C-reactive protein levels on adverse renal outcomes and mortality in patients undergoing surgery for AAAD. Methods Perioperative peak PCT, CRP, and IL-6 levels were retrospectively collected in 331 patients hospitalized with AAAD from 2009 to 2021. The primary endpoints were AKI stage 2–3 and mortality. The receiver operating characteristic (ROC) curves were used to compare the predictive values of peak PCT, CRP, and IL-6 for different clinical outcomes. Multivariable logistic regression analysis was used to find risk factors for AKI and 30-day mortality. Results The incidence of AKI stage 2–3 following AAAD was 50.8% (168/331). The 30-day and overall mortality were significantly greater in the AKI 2–3 group than in the AKI 0–1 group (P = 0.000). ROC curve analysis showed that peak PCT, with an area under the ROC curve (AUC) of 0.712, was a more accurate predictor of adverse renal outcomes than peak IL-6 and CRP. Multivariable logistic regression analysis revealed that PCT > 0.39 ng/mL was an independent risk factor for AKI stage 2–3. Peak IL-6 > 259 pg/mL was found to be an independent risk factor for 30-day mortality. Conclusion In patients with surgery for AAAD, peak PCT provides a well-predictive indicator of AKI stage 2–3 and peak IL-6 indicates a favorable predictor of 30-day mortality.